Impact of lameness on the milk production of ewes - Baranovič, Štefan; Tančin, Vladimír; Uhrinčať, Michail; Mačuhová, Lucia; Palkovič, Jozef (Acta Agraria Debreceniensis, 2016)
The aim of this study was assessing the impact of lameness on the milk production, somatic cells count and component of milk. We assess also impact of lameness on the order of entry into the milking parlour. The experiment was carried at the farm, located in northern Slovakia. The farm keeps sheep Improved Valachian. Samples of milk were taken during two periods: May, July. It was taken 428 samples together. We recorded three groups by lameness- strong lame, slightly lame, non-lame ewes. We recorded also the order of entry of ewes into the milking parlour in milking row. The results were mathematically processed using the Microsoft Excel program and statistically evaluated by SAS. We found significant statistical differences between months (P<0.0001) in all the above mentioned indicators. In July we recorded 26 ewes with slightly lameness and 18 ewes with strong lameness. Other ewes were non-lame. Non-lame sheep had in July the highest milk yield (356±148 ml) and the lowest decrease in milk yield from May to July (-206±131 ml) compared with slightly (317±116 ml, -223±163) and strong (319±122 ml, -219±151 ml) lame ewes. However, these differences were not statistically significant. We have not identified statistically significant differences between groups in somatic cells count (logxSCC for non-lame: 4.83±0.608 in ml, slightly lame: 4.76±0.653 in ml, strong lame 4.71±0.787 in ml). Milk composition (fat, proteins, lactose) nor changes in the composition of milk that occurred between May and July were not affected by lameness of ewes. But lameness in July affected the change the order of entry of ewes in the milking parlour in July compared with the order of entry recorded in May.